Strategi Cooperative Learning Tipe Student Teams Achievement Division (STAD) pada Mata Pelajaran Bahasa Arab - Muhammad Wahyudi; Abdul Rasyid Hidayat (Asatiza: Jurnal Pendidikan, 2021)
The Student Teams Achievement Division (STAD) strategy is very important in learning Arabic because this method is student-centered, active, cooperative, and helps each other complete assignments through discussion. The purpose of this study was to explore the literature on the STAD method in Arabic subjects. This paper was a literature study. The data showed that the STAD is simpler than other cooperative learning strategies; it is a good model for teachers who are just starting to apply cooperative strategies in learning. The teachers should give attention to each stage in STAD in innovative ways so that students do not feel bored and can increase their learning motivation and learning outcomes.